Calibration of rock cutting numerical model based on monitoring data - Pavlic, Vedran; Bacic, Mario; Kovacevic, Meho Sasa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Prediction of the deformation increment and the final displacement of the rock cutting is a challenging task. Many ambiguities linked with unpredictable nature or rock mass make it difficult to apply the adequate contingency measures. Implementation of common approach, which includes modelling of discontinuity effects with estimated reduction of rock mass strength and modulus of elasticity, usually does not yield satisfactory results. Therefore, a calibration of FEM based numerical model was made by conducting parametric analysis which feeds upon data obtained from extensive on-site monitoring system. A step forward was made in description of numerical parameters of karst discontinuities through consideration of monitoring results, as well as excavation procedures, position, inclination and length of discontinuities and PDC (project design change).